Pengembangan Wellness Tourism pada Pemandian Air Panas Lintang Tempuran Melalui Digital Marketing - Fathurrahman; Widiyanto, Nur; Sembada, Andhika Djalu (CV. Kurnia Grup, 2024)
Development of Wellness Tourism at the Lintang Tempuran hot springs inMagelang Regency through digital marketing, using descriptive qualitative research methods. The development of facilities at Lintang waterpark is already at a fairly good stage, where several facilities that visitors need are already available. From the results of field observations it was found that Lintang waterpark is already included in the standard of good facilities. As for several facilities at Lintang waterpark, such as a large parking area. , clean toilets, prayer areas, changing rooms. This research aims to explore the potential for developing wellness tourism at the Latitude Tempuran hot springs in Magelang district by utilizing digital marketing strategies. Based on the research results, several conclusions can be drawn, the Lintang Tempuran Hot Springs have great potential to become a wellness tourism destination. Digital marketing has a crucial role in increasing the visibility and accessibility of the Lintang Tempuran Hot Springs.